Growth potential of Listeria monocytogenes in artificially contaminated celery and chicken salad. (March 2017) - Sahu, Surasri N.; Kim, Bupmo; Ferguson, Martine S.; Zink, Don L.; Datta, Atin R.
Abstract: In a recent outbreak of listeriosis, celery, an ingredient of chicken salad, was identified as the vehicle for contamination. Epidemiological studies showed that the contaminated celery and chicken salad were contained with very low levels of L. monocytogenes. As infectious dose of L. monocytogens is considered to be high, questions were raised about the possibility of the of L. monocytogenes growth in these products before they were consumed. In this study the growth potential of three strains of L. monocytogenes representing three major serotypes were studied as a function of three different storage temperatures (5, 10 and 25 °C) and different incubation period (30 days at 5 °C, 12 days at 10 °C and 7 days at 25 °C) in cut celery and chicken salad prepared as per the recipe of the outbreak chicken salad. The growth of all three strains in celery and in laboratory made chicken salads was comparable. At 5 °C and 10 °C all three strains grew in celery by 1–2 log within 30 and 12 days, respectively. The growth of these strains under similar conditions in laboratory made chicken salad was 5–6 logs. The growth at 25 °C increased to 4–6 logs both in celery and laboratory made chicken salad within 3–4 days. These data show that celery and chicken salad can support L. monocytogenes growth and can reach high numbers even at refrigerated temperature if stored for a long time. Highlights: L. monocytogenes can survive and multiply in celery and chicken salad. Major disease causing serotypes of L. monocytogenes had similar growth potentials. Growth model indicates the risk associated with time-temp abuse with these products.